KEABSAHAN PUTUSAN PENGADILAN NEGERI SURABAYA NOMOR 117/PDT.SUS-PHI/2020/PN.SBY TENTANG PEMUTUSAN HUBUNGAN KERJA YANG DITINJAU DARI UNDANG-UNDANG CIPTA KERJA BESERTA PERATURAN PELAKSANANYA (STUDI KASUS : PT. WONOKOYO JAYA CORPORINDO) - Amadis Rasendhriya Yustiarachman; Soemali Soemali; Bambang Arwanto (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Humans as social beings generally have basic needs such as clothing, food and shelter. To fulfill these basic needs, humans are required to find a source of income, namely by working. In a job there is also a relationship called industrial relations. This study entitled "The Legitimacy of the Surabaya District Court Decision Number 117/Pdt.Sus-PHI/2020/PN.Sby Concerning Unilateral Termination of Employment (Case Study: PT. Wonokoyo Jaya Corporindo)" has a formulation of the problem, this problem include: what is the difference between termination of employment regulated in Law Number 13 of 2003 with Government Regulation in lieu of Law Number 2 of 2022, and whether the Surabaya District Court Decision Number 117/Pdt.Sus-PHI/2020/PN.Sby has used Law Number 11 of 2020 along with its implementing regulations. The results of this research analysis indicate that there are differences between Law Number 13 of 2003 and Government Regulation in lieu of Law Number 2 of 2022 regarding the amount of rights obtained for workers who have currently termination of employment due to disobey the company regulation and the judges of Surabaya District Court have not used provisions of Law Number 11 of 2020 and their implementing regulations